Measurement index system of specific physical training for tennis athletes - Li, Y.; Wang, J. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Tennis is a competitive sport endowed with subtle movements, sophisticated and changeable techniques and tactics, and intense confrontation. It has high demands on the athlete's physical and psychological qualities. To win high-level professional tennis events, in addition to basic skills, comprehensive technical and tactical abilities, stable psychological quality, and flexible and innovative thinking, tennis players must also have exceptional physical fitness. Objective: Study the index system for evaluating the sport-specific skills of tennis athletes. Methods: 30 youth tennis training athletes were selected. Research methods such as literature, expert interview, questionnaire, and mathematical statistics were used to construct the fitness evaluation index of Chinese professional tennis players. Results: Professional tennis players` specific fitness assessment indexes include one first-level index, 14 second-level indexes, and 23 three-item indexes. Conclusion: Young athletes must strengthen their agile attack speed, explosive strength, core strength, and coordination. The individual indicators are weighted according to individual standards of physical training level. Thus, the five first-level indicators and specific fitness standards are established in this paper. The results of this research have guiding significance for the formulation and implementation of further tennis education and training plans.